Brand preferences of perodua cars : a case study in Sibu/Saadon Hj Zamhari - Zamhari, Saadon
The purpose of the study is to make a research on brand preferences for difference car models of Perodua brand in Sibu. The research include identifyingthe extent of brand preferences for one Perodua Brand namely Kancil, Kelisa, Rusa, Kembara, Kenari and Myvi. The focus of the subject is the Perodua car buyers in Sibu from whom the author has distributed questionnaires and gathered relevant information. In addition, a research is made on the number of car registered in Sibu based on the statistic obtained from the Road Transport Department Sibu for the year 2003 to 2005. To support the finding, the author has also gathered some data related to the number of various Perodua cars sold in Sibu throughout the same period from a Perodua car dealer in Sibu, Ngu Chung Beng And Sons Sendirian Berhad.